2017
DOI: 10.1111/liv.13539
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature fluctuation analysis in cirrhosis

Abstract: We recently reported that patients with cirrhosis exhibit an abnormal pattern in their skin temperature variability, with complexity analysis of skin temperature fluctuations distinguishing inpatients from outpatients, despite similar mean temperature values [1]. Patients with cirrhosis also exhibit abnormalities in circadian rhythmicity, part of which are of central origin [2]. Therefore, we wondered if abnormalities in skin temperature fluctuations may reflect abnormalities in core body temperature (CBT) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Additionally, as recent studies have showed thermoregulatory impairment in cirrhotic patients both in skin temperature recordings and core body temperature readings (30,31).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, as recent studies have showed thermoregulatory impairment in cirrhotic patients both in skin temperature recordings and core body temperature readings (30,31).…”
Section: Discussionmentioning
confidence: 98%
“…This has been postulated to be due to systemic vasodilation, as a result of the extensive release of endogenous vasodilators or due to the autonomic dysfunction observed in patients with cirrhosis, thus highlighting that cirrhotic patients' temperature variability profile does indeed change and is suggestive of altered thermoregulatory function, compared to healthy individuals. Mani et al also revealed that cirrhotic rats exhibit greater entropy in their core body temperature, compared to control rats, possibly indicative of an increased amount of coupling and information processing in the thermoregulatory system (Mani et al, 2018). Based on these recent studies there is evidence to suggest that cirrhosis is associated with an altered pattern in the fluctuations of patients' body temperature profile, which may indeed be correlated with multisystem involvement of cirrhosis.…”
Section: Introductionmentioning
confidence: 97%
“…A variety of different computational methods have been developed to analyze fluctuations in patients' body temperature, as well as experimental models (Ahmed et al, 2010;Mani, Mazloom, Haddadian, & Montagnese, 2018;Papaioannou et al, 2012;Satti et al, 2019). It appears that body temperature fluctuation analysis can provide crucial information regarding the integrity of one's thermoregulatory system (Mani et al, 2018;Satti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations